2009
DOI: 10.1179/016164108x323771
|View full text |Cite
|
Sign up to set email alerts
|

Expression of amyloid precursor protein after rat traumatic brain injury

Abstract: These results suggested that long-term overexpression of APP was confirmed by immunohistochemical and biologic technique after TBI. This may be related to the induction of Alzheimer type dementia and it is a very important risk factor for this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 29 publications
1
47
1
Order By: Relevance
“…Both axonal and neuronal abnormalities were identified that were broadly similar to findings reported in other forms of TBI (Blumbergs et al, 1995;Bramlett et al, 1997;Itoh et al, 2009;Kilbourne et al, 2009;Pierce et al, 1996;Stone et al, 2000). Abnormalities in b-APP were widespread, and involved deep brain regions away from subarachnoid hemorrhages.…”
Section: Prough 2009) Understanding This Complex Relationship Is Ofsupporting
confidence: 61%
“…Both axonal and neuronal abnormalities were identified that were broadly similar to findings reported in other forms of TBI (Blumbergs et al, 1995;Bramlett et al, 1997;Itoh et al, 2009;Kilbourne et al, 2009;Pierce et al, 1996;Stone et al, 2000). Abnormalities in b-APP were widespread, and involved deep brain regions away from subarachnoid hemorrhages.…”
Section: Prough 2009) Understanding This Complex Relationship Is Ofsupporting
confidence: 61%
“…APP expression has been shown to increase after neuronal injury due to TBI (Itoh et al, 2009;Murakami et al, 1998;Otsuka et al, 1991). The effect of the anti-CD11d treatment on neuronal damage was assessed in homogenates of the rat brains using Western blot analysis (Fig.…”
Section: Amyloid Precursor Protein (App)mentioning
confidence: 99%
“…19,109 Furthermore, several studies have provided experimental evidence that traumatic head injury in rodents and humans can result in significant elevation in APP levels, 110,111 as well as Aβ generation and amyloid plaque deposition. 112,113 In line with the high turnover, rapid anterograde transport, and processing of APP in distal compartments, [114][115][116] genetically induced fibre tract degeneration in the gracile axonal dystrophy mouse provokes rapid axonal accumulation of APP and Aβ.…”
Section: Inflammation and Cellular Stressmentioning
confidence: 99%